From QTL to candidate genes: a data-driven approach to unravel the genetic architecture of yellow rust resistance in central European wheat - Jiaojiao Wang; Renate H. Schmidt; Guoliang Li; Albrecht Serfling; Jochen C. Reif; Yong Jiang (Theoretical and Applied Genetics, 2026)
Key message A data mining strategy capitalizing on high-resolution SNP information, sequence variant annotation and QTL information from three populations facilitated an efficient nomination of candidate genes for YR resistance, supported by Yr27 and functional annotations. Abstract Genome-wide association studies (GWAS) have become routine in many crops, but the prioritization of candidate genes remains challenging. Here, we developed a new approach to identify environment-specific quantitative trait loci (QTL) using GWAS and analyzed 5,840 wheat genotypes distributed over three experimental populations, including 5,243 single-cross hybrids and 597 elite lines. Resequencing the parental genotypes identified over 640,000 single-nucleotide polymorphisms (SNPs) after filtering. The hybrid panels were tested in 19 environments for susceptibility to Puccinia striiformis f. sp. tritici ( Pst ), a pathogen responsible for severe yellow rust (YR) epidemics especially after 2012. QTL patterns in diverse environments showed substantial differences, reflecting spatial and temporal dynamics. Combining high-resolution SNP information, sequence variant annotation and QTL information from different populations obtained via a novel GWAS approach enabled the efficient nomination of candidate genes for YR resistance loci of particular relevance for Central European wheat. The power of the developed strategy for mining data from different experimental populations was demonstrated as the validated resistance gene Yr27 was identified as sole candidate gene for one QTL region.

Reassessing data management in increasingly complex phenotypic datasets - Cyril Pommier; Isabelle Alic; Llorenç Cabrera-Bosquet; Xavier Draye; Pascal Neveu; Jochen C. Reif; Kelly R. Robbins; Pawel Krajewski; François Tardieu (Trends in Plant Science, 2026)

Association mapping of hybrid seed set and heterosis in a central European multi-parental wheat population - Sandra L. Zapata; Vilson Mirdita; Philipp H. G. Boeven; Pierrick Varenne; Monika Spiller; Shobhashree Nagireddy; Mario Gils; Jochen C. Reif; Guoliang Li (Theoretical and Applied Genetics, 2026)
Key Message Heterosis in wheat results from a complex interplay of dominance and epistasis, with epistasis playing a major role, underscoring the genetic complexity and challenges in systematically exploiting hybrid vigor. Abstract The systematic exploitation of heterosis has the potential to increase wheat yields by around 10% compared to inbred lines. However, the lack of natural cross-pollination in wheat significantly increases the cost of producing hybrid seeds. Our study aimed to address these issues by identifying indirect traits that enhance pollination efficiency in hybrid seed production and by genetically dissecting heterosis for key agronomic traits in the resulting hybrids. We evaluated the pollen donor capacity of 294 doubled haploid (DH) lines derived from ten biparental populations adapted to Central European conditions. While no universally applicable indirect predictors of pollination ability were identified, we found that population-specific traits correlated with pollinator performance. We evaluated the resulting hybrids and their parental lines in multi-location field trials for grain yield, plant height, heading date, and susceptibility to yellow and leaf rust. Quantitative trait locus (QTL) analysis revealed that heterosis in wheat is governed by a complex interplay of dominance effects and epistatic interactions. The relative contribution of these genetic effects varies significantly across traits and populations. Epistasis notably played a substantial role in heterosis, emphasizing the genetic complexity of wheat and explaining the challenges associated with its systematic exploitation.

Targeted expansion of a barley genebank core collection facilitates the discovery of disease resistance loci - Zhihui Yuan; Yusheng Zhao; Klaus Oldach; Ahmed Jahoor; Jens Due Jensen; Viktoria-Elisabeth Dohrendorf; Tobias W. Eschholz; Sabrina Roescher; Nils Stein; Jochen C. Reif; Samira El Hanafi (Theoretical and Applied Genetics, 2026)
Utilizing the diversity preserved in genebank collections is essential for accelerating crop improvement, yet information is often limited to selected core collections. Genome-wide prediction (GWP) offers a promising approach to large-scale phenotypic imputation, with proven utility in practical pre-breeding contexts. In this study, we leveraged GWP to expand the German Federal ex situ barley core collection (core1000) with a focus on resistance to Puccinia hordei , Blumeria graminis hordei , and Rhynchosporium commune . Using the barley core1000 collection, which was originally selected to maximize molecular diversity, we trained genomic prediction models and imputed resistance scores for 20,458 genebank accessions based on sequence data encompassing 306,049 high-quality SNPs. To empirically validate prediction accuracy, we selected 300 spring and winter barley genotypes for field evaluation across four environments, resulting in moderate-to-strong correlations between predicted and observed resistance levels. Genome-wide association mapping in this set revealed five marker–trait associations that were not detected in the original core1000 collection. These results demonstrate that prediction-informed sampling can effectively expand trait-relevant genetic diversity and increase the frequency of resistance-associated alleles, thereby improving the power to detect loci that may be overlooked in conventional panels. Accordingly, GWP supports the targeted inclusion of accessions with trait-relevant variation and enhances the value of genebank resources for trait discovery and pre-breeding applications.

Order from entropy: big data from FAIR data cohorts in the digital age of plant breeding - Abhishek Gogna; Daniel Arend; Sebastian Beier; Ehsan Eyshi Rezaei; Tobias Würschum; Yusheng Zhao; Jianting Chu; Jochen C. Reif (Theoretical and Applied Genetics, 2025)
Lack of interoperable datasets in plant breeding research creates an innovation bottleneck, requiring additional effort to integrate diverse datasets—if access is possible at all. Handling of plant breeding data and metadata must, therefore, change toward adopting practices that promote openness, collaboration, standardization, ethical data sharing, sustainability, and transparency of provenance and methodology. FAIR Digital Objects, which build on research data infrastructures and FAIR principles, offer a path to address this interoperability crisis, yet their adoption remains in its infancy. In the present work, we identify data sharing practices in the plant breeding domain as Data Cohorts and establish their connection to FAIR Digital Objects. We further link these cohorts to broader research infrastructures and propose a Data Trustee model for federated data sharing. With this we aim to push the boundaries of data management, often viewed as the last step in plant breeding research, to an ongoing process to enable future innovations in the field.

Genetic control and prospects of predictive breeding for European winter wheat’s Zeleny sedimentation values and Hagberg-Perten falling number - Quddoos H. Muqaddasi; Roop Kamal Muqaddasi; Erhard Ebmeyer; Viktor Korzun; Odile Argillier; Vilson Mirdita; Jochen C. Reif; Martin W. Ganal; Marion S. Röder (Theoretical and Applied Genetics, 2023)
Key message Sedimentation values and falling number in the last decades have helped maintain high baking quality despite rigorous selection for grain yield in wheat. Allelic combinations of major loci sustained the bread-making quality while improving grain yield. Glu-D1 , Pinb-D1 , and non-gluten proteins are associated with sedimentation values and falling number in European wheat. Abstract Zeleny sedimentation values (ZSV) and Hagberg-Perten falling number (HFN) are among the most important parameters that help determine the baking quality classes of wheat and, thus, influence the monetary benefits for growers. We used a published data set of 372 European wheat varieties evaluated in replicated field trials in multiple environments. ZSV and HFN traits hold a wide and significant genotypic variation and high broad-sense heritability. The genetic correlations revealed positive and significant associations of ZSV and HFN with each other, grain protein content (GPC) and grain hardness; however, they were all significantly negatively correlated with grain yield. Besides, GPC appeared to be the major predictor for ZSV and HFN. Our genome-wide association analyses based on high-quality SSR, SNP, and candidate gene markers revealed a strong quantitative genetic nature of ZSV and HFN by explaining their total genotypic variance as 41.49% and 38.06%, respectively. The association of known Glutenin ( Glu-1 ) and Puroindoline (Pin-1) with ZSV provided positive analytic proof of our studies. We report novel candidate loci associated with globulins and albumins—the non-gluten monomeric proteins in wheat. In addition, predictive breeding analyses for ZSV and HFN suggest using genomic selection in the early stages of breeding programs with an average prediction accuracy of 81 and 59%, respectively.

Maximization through optimization? On the relationship between hybrid performance and parental genetic distance - Tobias Würschum; Xintian Zhu; Yusheng Zhao; Yong Jiang; Jochen C. Reif; Hans Peter Maurer (Theoretical and Applied Genetics, 2023)
Heterosis is the improved performance of hybrids compared with their parental components and is widely exploited in agriculture. According to quantitative genetic theory, genetic distance between parents at heterotic quantitative trait loci is required for heterosis, but how heterosis varies with genetic distance has remained elusive, despite intensive research on the topic. Experimental studies have often found a positive association between heterosis and genetic distance that, however, varied in strength. Most importantly, it has remained unclear whether heterosis increases continuously with genetic distance or whether there is an optimum genetic distance after which heterosis declines again. Here, we revisit the relationship between heterosis and genetic distance and provide perspectives on how to maximize heterosis and hybrid performance in breeding, as well as the consequences for the design of heterotic groups and the utilization of more exotic material and genetic resources.

Deciphering the genetic basis of resistance to soybean cyst nematode combining IBD and association mapping - Yu Tian; Delin Li; Xueqing Wang; Hao Zhang; Jiajun Wang; Lijie Yu; Changhong Guo; Xiaoyan Luan; Xinlei Liu; Hongjie Li; Jochen C. Reif; Ying-hui Li; et al. (Theoretical and Applied Genetics, 2023)
Key message IBD analysis clarified the dynamics of chromosomal recombination during the ZP pedigree breeding process and identified ten genomic regions resistant to SCN race3 combining association mapping. Abstract Soybean cyst nematode (SCN, Heterodera glycines Ichinohe) is one of the most devastating pathogens for soybean production worldwide. The cultivar Zhongpin03-5373 (ZP), derived from SCN-resistant progenitor parents, Peking, PI 437654 and Huipizhi Heidou, is an elite line with high resistance to SCN race3. In the current study, a pedigree variation map was generated for ZP and its ten progenitors using 3,025,264 high-quality SNPs identified from an average of 16.2 × re-sequencing for each genome. Through identity by decent (IBD) tracking, we showed the dynamic change of genome and detected important IBD fragments, which revealed the comprehensively artificial selection of important traits during ZP breeding process. A total of 2,353 IBD fragments related to SCN resistance including SCN-resistant genes rhg1 , rhg4 and NSF RAN07 were identified based on the resistant-related genetic paths. Moreover, 23 genomic regions underlying resistance to SCN race3 were identified by genome-wide association study (GWAS) in 481 re-sequenced cultivated soybeans. Ten common loci were found by both IBD tracking and GWAS analysis. Haplotype analysis of 16 potential candidate genes suggested a causative SNP (C/T, − 1065) located in the promoter of Glyma.08G096500 and encoding a predicted TIFY5b-related protein on chr8 was highly correlated with SCN race3 resistance. Our results more thoroughly elucidated the dynamics of genomic fragments during ZP pedigree breeding and the genetic basis of SCN resistance, which will provide useful information for gene cloning and the development of resistant soybean cultivars using a marker-assisted selection approach.

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Choosing the right tool: Leveraging of plant genetic resources in wheat (Triticum aestivum L.) benefits from selection of a suitable genomic prediction model - Marcel O. Berkner; Albert W. Schulthess; Yusheng Zhao; Yong Jiang; Markus Oppermann; Jochen C. Reif (Theoretical and Applied Genetics, 2022)
Key message Genomic prediction of genebank accessions benefits from the consideration of additive-by-additive epistasis and subpopulation-specific marker effects. Abstract Wheat ( Triticum aestivum L.) and other species of the Triticum genus are well represented in genebank collections worldwide. The substantial genetic diversity harbored by more than 850,000 accessions can be explored for their potential use in modern plant breeding. Characterization of these large number of accessions is constrained by the required resources, and this fact limits their use so far. This limitation might be overcome by engaging genomic prediction. The present study compared ten different genomic prediction approaches to the prediction of four traits, namely flowering time, plant height, thousand grain weight, and yellow rust resistance, in a diverse set of 7745 accession samples from Germany’s Federal ex situ genebank at the Leibniz Institute of Plant Genetics and Crop Plant Research in Gatersleben. Approaches were evaluated based on prediction ability and robustness to the confounding influence of strong population structure. The authors propose the wide application of extended genomic best linear unbiased prediction due to the observed benefit of incorporating additive-by-additive epistasis. General and subpopulation-specific additive ridge regression best linear unbiased prediction, which accounts for subpopulation-specific marker-effects, was shown to be a good option if contrasting clusters are encountered in the analyzed collection. The presented findings reaffirm that the trait’s genetic architecture as well as the composition and relatedness of the training set and test set are major driving factors for the accuracy of genomic prediction.

Hybrid wheat: quantitative genetic parameters and heterosis for quality and rheological traits as well as baking volume - Lea Schwarzwälder; Patrick Thorwarth; Yusheng Zhao; Jochen Christoph Reif; C. Friedrich H. Longin (Theoretical and Applied Genetics, 2022)
Key message Heterosis effects for dough quality and baking volume were close to zero. However, hybrids have a higher grain yield at a given level of bread making quality compared to their parental lines. Abstract Bread wheat cultivars have been selected according to numerous quality traits to fulfill the requirements of the bread making industry. These include beside protein content and quality also rheological traits and baking volume. We evaluated 35 male and 73 female lines and 119 of their single-cross hybrids at three different locations for grain yield, protein content, sedimentation value, extensograph traits and baking volume. No significant differences ( p < 0.05) were found in the mean comparisons of males, females and hybrids, except for higher grain yield and lower protein content in the hybrids. Mid-parent and better-parent heterosis values were close to zero and slightly negative, respectively, for baking volume and extensograph traits. However, the majority of heterosis values resulted in the finding that hybrids had higher grain yield than lines for a given level of baking volume, sedimentation value or energy value of extensograph. Due to the high correlation with the mid-parent values ( r > 0.70), an initial prediction of hybrid performance based on line per se performance for protein content, sedimentation value, most traits of the extensograph and baking volume is possible. The low variance due to specific combining ability effects for most quality traits points toward an additive gene action requires quality selection within both heterotic groups. Consequently, hybrid wheat can combine high grain yield with high bread making quality. However, the future use of wheat hybrids strongly depends on the establishment of a cost-efficient and reliable seed production system.

Genomic prediction models trained with historical records enable populating the German ex situ genebank bio-digital resource center of barley (Hordeum sp.) with information on resistances to soilborne barley mosaic viruses - Maria Y. Gonzalez; Yusheng Zhao; Yong Jiang; Nils Stein; Antje Habekuss; Jochen C. Reif; Albert W. Schulthess (Theoretical and Applied Genetics, 2021)
Key message Genomic prediction with special weight of major genes is a valuable tool to populate bio-digital resource centers. Abstract Phenotypic information of crop genetic resources is a prerequisite for an informed selection that aims to broaden the genetic base of the elite breeding pools. We investigated the potential of genomic prediction based on historical screening data of plant responses against the Barley yellow mosaic viruses for populating the bio-digital resource center of barley. Our study includes dense marker data for 3838 accessions of winter barley, and historical screening data of 1751 accessions for Barley yellow mosaic virus (BaYMV) and of 1771 accessions for Barley mild mosaic virus (BaMMV). Linear mixed models were fitted by considering combinations for the effects of genotypes, years, and locations. The best linear unbiased estimations displayed a broad spectrum of plant responses against BaYMV and BaMMV. Prediction abilities, computed as correlations between predictions and observed phenotypes of accessions, were low for the marker-assisted selection approach amounting to 0.42. In contrast, prediction abilities of genomic best linear unbiased predictions were high, with values of 0.62 for BaYMV and 0.64 for BaMMV. Prediction abilities of genomic prediction were improved by up to ~ 5% using W-BLUP, in which more weight is given to markers with significant major effects found by association mapping. Our results outline the utility of historical screening data and W-BLUP model to predict the performance of the non-phenotyped individuals in genebank collections. The presented strategy can be considered as part of the different approaches used in genebank genomics to valorize genetic resources for their usage in disease resistance breeding and research.

Genomics and breeding innovations for enhancing genetic gain for climate resilience and nutrition traits - Pallavi Sinha; Vikas K. Singh; Abhishek Bohra; Arvind Kumar; Jochen C. Reif; Rajeev K. Varshney (Theoretical and Applied Genetics, 2021)
Key message Integrating genomics technologies and breeding methods to tweak core parameters of the breeder’s equation could accelerate delivery of climate-resilient and nutrient rich crops for future food security. Abstract Accelerating genetic gain in crop improvement programs with respect to climate resilience and nutrition traits, and the realization of the improved gain in farmers’ fields require integration of several approaches. This article focuses on innovative approaches to address core components of the breeder’s equation. A prerequisite to enhancing genetic variance ( σ 2 g ) is the identification or creation of favorable alleles/haplotypes and their deployment for improving key traits. Novel alleles for new and existing target traits need to be accessed and added to the breeding population while maintaining genetic diversity. Selection intensity ( i ) in the breeding program can be improved by testing a larger population size, enabled by the statistical designs with minimal replications and high-throughput phenotyping. Selection priorities and criteria to select appropriate portion of the population too assume an important role. The most important component of breeder′s equation is heritability ( h 2 ). Heritability estimates depend on several factors including the size and the type of population and the statistical methods. The present article starts with a brief discussion on the potential ways to enhance σ 2 g in the population. We highlight statistical methods and experimental designs that could improve trait heritability estimation. We also offer a perspective on reducing the breeding cycle time ( t ), which could be achieved through the selection of appropriate parents, optimizing the breeding scheme, rapid fixation of target alleles, and combining speed breeding with breeding programs to optimize trials for release. Finally, we summarize knowledge from multiple disciplines for enhancing genetic gains for climate resilience and nutritional traits.

The potential of hybrid breeding to enhance leaf rust and stripe rust resistance in wheat - Ulrike Beukert; Guozheng Liu; Patrick Thorwarth; Philipp H. G. Boeven; C. Friedrich H. Longin; Yusheng Zhao; Martin Ganal; Albrecht Serfling; Frank Ordon; Jochen C. Reif (Theoretical and Applied Genetics, 2020)
Key message Hybrid wheat breeding is a promising strategy to improve the level of leaf rust and stripe rust resistance in wheat. Abstract Leaf rust and stripe rust belong to the most important fungal diseases in wheat production. Due to a dynamic development of new virulent races, epidemics appear in high frequency and causes significant losses in grain yield and quality. Therefore, research is needed to develop strategies to breed wheat varieties carrying highly efficient resistances. Stacking of dominant resistance genes through hybrid breeding is such an approach. Within this study, we investigated the genetic architecture of leaf rust and stripe rust resistance of 1750 wheat hybrids and their 230 parental lines using a genome-wide association study. We observed on average a lower rust susceptibility for hybrids in comparison to their parental inbred lines and some hybrids outperformed their better parent with up to 56%. Marker-trait associations were identified on chromosome 3D and 4A for leaf rust and on chromosome 2A, 2B, and 6A for stripe rust resistance by using a genome-wide association study with a Bonferroni-corrected threshold of P < 0.10. Detected loci on chromosomes 4A and 2A were located within previously reported genomic regions affecting leaf rust and stripe rust resistance, respectively. The degree of dominance was for most associations favorable in the direction of improved resistance. Thus, resistance can be increased in hybrid wheat breeding by fixing complementary leaf rust and stripe rust resistance genes with desired dominance effects in opposite parental pools.

Reciprocal recurrent genomic selection: an attractive tool to leverage hybrid wheat breeding - Maximilian Rembe; Yusheng Zhao; Yong Jiang; Jochen C. Reif (Theoretical and Applied Genetics, 2019)

Unlocking historical phenotypic data from an ex situ collection to enhance the informed utilization of genetic resources of barley (Hordeum sp.) - Maria Y. González; Norman Philipp; Albert W. Schulthess; Stephan Weise; Yusheng Zhao; Andreas Börner; Markus Oppermann; Andreas Graner; Jochen C. Reif (Theoretical and Applied Genetics, 2018)

Exploiting the Rht portfolio for hybrid wheat breeding - Tobias Würschum; Guozheng Liu; Philipp H. G. Boeven; C. Friedrich H. Longin; Vilson Mirdita; Ebrahim Kazman; Yusheng Zhao; Jochen C. Reif (Theoretical and Applied Genetics, 2018)

Advantages and limitations of multiple-trait genomic prediction for Fusarium head blight severity in hybrid wheat (Triticum aestivum L.) - Albert W. Schulthess; Yusheng Zhao; C. Friedrich H. Longin; Jochen C. Reif (Theoretical and Applied Genetics, 2018)

Genome-wide mapping and prediction suggests presence of local epistasis in a vast elite winter wheat populations adapted to Central Europe - Sang He; Jochen C. Reif; Viktor Korzun; Reiner Bothe; Erhard Ebmeyer; Yong Jiang (Theoretical and Applied Genetics, 2017)

Validating the prediction accuracies of marker-assisted and genomic selection of Fusarium head blight resistance in wheat using an independent sample - Yong Jiang; Albert Wilhelm Schulthess; Bernd Rodemann; Jie Ling; Jörg Plieske; Sonja Kollers; Erhard Ebmeyer; Viktor Korzun; Odile Argillier; Gunther Stiewe; Martin W. Ganal; Marion S. Röder; et al. (Theoretical and Applied Genetics, 2017)

Genome-wide association mapping and genome-wide prediction of anther extrusion in CIMMYT spring wheat - Quddoos H. Muqaddasi; Jochen C. Reif; Zou Li; Bhoja R. Basnet; Susanne Dreisigacker; Marion S. Röder (Euphytica, 2017)

High accuracy of predicting hybrid performance of Fusarium head blight resistance by mid-parent values in wheat - Thomas Miedaner; Albert W. Schulthess; Manje Gowda; Jochen C. Reif; C. Friedrich H. Longin (Theoretical and Applied Genetics, 2017)

Genomic selection in a commercial winter wheat population - Sang He; Albert Wilhelm Schulthess; Vilson Mirdita; Yusheng Zhao; Viktor Korzun; Reiner Bothe; Erhard Ebmeyer; Jochen C. Reif; Yong Jiang (Theoretical and Applied Genetics, 2016)

Multiple-trait- and selection indices-genomic predictions for grain yield and protein content in rye for feeding purposes - Albert Wilhelm Schulthess; Yu Wang; Thomas Miedaner; Peer Wilde; Jochen C. Reif; Yusheng Zhao (Theoretical and Applied Genetics, 2016)

Potential and limits of whole genome prediction of resistance to Fusarium head blight and Septoria tritici blotch in a vast Central European elite winter wheat population - Vilson Mirdita; Sang He; Yusheng Zhao; Viktor Korzun; Reiner Bothe; Erhard Ebmeyer; Jochen C. Reif; Yong Jiang (Theoretical and Applied Genetics, 2015)

Optimum allocation of test resources and comparison of breeding strategies for hybrid wheat - C. Friedrich H. Longin; Xuefei Mi; Albrecht E. Melchinger; Jochen C. Reif; Tobias Würschum (Theoretical and Applied Genetics, 2014)

Long-term perspective of hybrid versus line breeding in wheat based on quantitative genetic theory - C. Friedrich H. Longin; Jochen C. Reif; Tobias Würschum (Theoretical and Applied Genetics, 2014)

Multiple-line cross QTL mapping for biomass yield and plant height in triticale (× Triticosecale Wittmack) - Katharina V. Alheit; Lucas Busemeyer; Wenxin Liu; Hans Peter Maurer; Manje Gowda; Volker Hahn; Sigrid Weissmann; Arno Ruckelshausen; Jochen C. Reif; Tobias Würschum (Theoretical and Applied Genetics, 2014)

Association between line per se and testcross performance for eight agronomic and quality traits in winter rye - Thomas Miedaner; Diana D. Schwegler; Peer Wilde; Jochen C. Reif (Theoretical and Applied Genetics, 2014)

Population structure, genetic diversity and linkage disequilibrium in elite winter wheat assessed with SNP and SSR markers - Tobias Würschum; Simon M. Langer; C. Friedrich H. Longin; Viktor Korzun; Eduard Akhunov; Erhard Ebmeyer; Ralf Schachschneider; Johannes Schacht; Ebrahim Kazman; Jochen C. Reif (Theoretical and Applied Genetics, 2013)

Best linear unbiased prediction of triticale hybrid performance - Manje Gowda; Yusheng Zhao; Hans Peter Maurer; Elmar A. Weissmann; Tobias Würschum; Jochen C. Reif (Euphytica, 2013)

Hybrid rye performance under natural drought stress in Europe - Marlen Hübner; Peer Wilde; Brigitta Schmiedchen; Pawel Dopierala; Manje Gowda; Jochen C. Reif; Thomas Miedaner (Theoretical and Applied Genetics, 2013)

Effect of inter- and intragenic epistasis on the heritability of oil content in rapeseed (Brassica napus L.) - Tobias Würschum; Hans Peter Maurer; Felix Dreyer; Jochen C. Reif (Theoretical and Applied Genetics, 2013)

Detection of QTL for flowering time in multiple families of elite maize - Jana Steinhoff; Wenxin Liu; Jochen C. Reif; Giovanni Della Porta; Nicolas Ranc; Tobias Würschum (Theoretical and Applied Genetics, 2012)

Mapping QTLs for root system architecture of maize (Zea mays L.) in the field at different developmental stages - Hongguang Cai; Fanjun Chen; Guohua Mi; Fusuo Zhang; Hans Peter Maurer; Wenxin Liu; Jochen C. Reif; Lixing Yuan (Theoretical and Applied Genetics, 2012)

Comparison of biometrical approaches for QTL detection in multiple segregating families - Wenxin Liu; Jochen C. Reif; Nicolas Ranc; Giovanni Della Porta; Tobias Würschum (Theoretical and Applied Genetics, 2012)

Impact of selective genotyping in the training population on accuracy and bias of genomic selection - Yusheng Zhao; Manje Gowda; Friedrich H. Longin; Tobias Würschum; Nicolas Ranc; Jochen C. Reif (Theoretical and Applied Genetics, 2012)

Accuracy of genomic selection in European maize elite breeding populations - Yusheng Zhao; Manje Gowda; Wenxin Liu; Tobias Würschum; Hans P. Maurer; Friedrich H. Longin; Nicolas Ranc; Jochen C. Reif (Theoretical and Applied Genetics, 2012)

Dissecting the genetic architecture of agronomic traits in multiple segregating populations in rapeseed (Brassica napus L.) - Tobias Würschum; Wenxin Liu; Hans Peter Maurer; Stefan Abel; Jochen C. Reif (Theoretical and Applied Genetics, 2012)

Mapping QTLs with main and epistatic effects underlying grain yield and heading time in soft winter wheat - Jochen C. Reif; Hans P. Maurer; Viktor Korzun; Erhard Ebmeyer; T. Miedaner; Tobias Würschum (Theoretical and Applied Genetics, 2011)

Extent and genome-wide distribution of linkage disequilibrium in commercial maize germplasm - Delphine Van Inghelandt; Jochen C. Reif; Baldev S. Dhillon; Pascal Flament; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2011)

Association mapping for quality traits in soft winter wheat - Jochen C. Reif; Manje Gowda; Hans P. Maurer; C. F. H. Longin; Viktor Korzun; Erhard Ebmeyer; Reiner Bothe; Christof Pietsch; Tobias Würschum (Theoretical and Applied Genetics, 2011)

Genetic basis of agronomically important traits in sugar beet (Beta vulgaris L.) investigated with joint linkage association mapping - Jochen C. Reif; Wenxin Liu; Manje Gowda; Hans Peter Maurer; Jens Möhring; Sandra Fischer; Axel Schechert; Tobias Würschum (Theoretical and Applied Genetics, 2010)

Broadening the genetic base of European maize heterotic pools with US Cornbelt germplasm using field and molecular marker data - Jochen C. Reif; Sandra Fischer; Tobias A. Schrag; Kendall R. Lamkey; Dietrich Klein; Baldev S. Dhillon; H. Friedrich Utz; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2010)

Hybrid maize breeding with doubled haploids. IV. Number versus size of crosses and importance of parental selection in two-stage selection for testcross performance - Thilo Wegenast; C. Friedrich H. Longin; H. Friedrich Utz; Albrecht E. Melchinger; Hans Peter Maurer; Jochen C. Reif (Theoretical and Applied Genetics, 2008)

Hybrid maize breeding with doubled haploids: III. Efficiency of early testing prior to doubled haploid production in two-stage selection for testcross performance - C. Friedrich H. Longin; H. Friedrich Utz; Jochen C. Reif; Thilo Wegenast; Wolfgang Schipprack; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2007)

Potential causes of linkage disequilibrium in a European maize breeding program investigated with computer simulations - Benjamin Stich; Albrecht E. Melchinger; Hans-Peter Piepho; Sonia Hamrit; Wolfgang Schipprack; Hans P. Maurer; Jochen C. Reif (Theoretical and Applied Genetics, 2007)

Hybrid maize breeding with doubled haploids: II. Optimum type and number of testers in two-stage selection for general combining ability - C. Friedrich H. Longin; H. Friedrich Utz; Albrecht E. Melchinger; Jochen C. Reif (Theoretical and Applied Genetics, 2007)

A new test for family-based association mapping with inbred lines from plant breeding programs - Benjamin Stich; Albrecht E. Melchinger; Hans-Peter Piepho; Martin Heckenberger; Hans P. Maurer; Jochen C. Reif (Theoretical and Applied Genetics, 2006)

Hybrid maize breeding with doubled haploids: I. One-stage versus two-stage selection for testcross performance - C. Friedrich H. Longin; H. Friedrich Utz; Jochen C. Reif; Wolfgang Schipprack; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2006)

New editorial office - Heiko C. Becker; Christian Möllers; Albrecht E. Melchinger; Eva Bauer; Jochen C. Reif (Theoretical and Applied Genetics, 2005)

Genetic structure and diversity of European flint maize populations determined with SSR analyses of individuals and bulks - Jochen C. Reif; Sonia Hamrit; Martin Heckenberger; Wolfgang Schipprack; Hans Peter Maurer; Martin Bohn; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2005)

Trends in genetic diversity among European maize cultivars and their parental components during the past 50 years - Jochen C. Reif; Sonia Hamrit; Martin Heckenberger; Wolfgang Schipprack; Hans Peter Maurer; Martin Bohn; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2005)

Linkage disequilibrium in European elite maize germplasm investigated with SSRs - Benjamin Stich; Albrecht E. Melchinger; Matthias Frisch; Hans P. Maurer; Martin Heckenberger; Jochen C. Reif (Theoretical and Applied Genetics, 2005)